A Multipurpose Computer Package for Medium Sized Construction Firms in Nigeria - Osibodu, Anthony B. (Obafemi Awolowo University, 2014)
The purpose of this study is to examine how the computer can be of assistance in the management of medium sized construction firms in Nigeria. The first part of the investigations was undertaken by carrying out extensive literature reviews on the uses of computer in the management of the construction industry with particular reference to medium sized construction firms in Nigeria. The second part was carried out using questionnaires administered to construction management personnel and computer vendors in various parts of the country, to ascertain the current uses of the computer in the Nigerian Building Industry. These investigations revealed that accounting and estimating procedures in medium sized construction firms could be improved if computerized. In the third part computerized samples of these procedures were presented. In order to facilitate the uses of these computerized procedures it was finally suggested that computer training be given to construction management personnel; that in the selection of computer vendors, the user must be assured support for maintenance of both hardware and software; and that the government's attitude should change towards the computer which it regards as imported goods and not technology.